Mean Inequalities for Derivatives of the Generalised Exponential Integral Function - Iddi, Rahamatu; Nantomah, Kwara; Zubil, Morgan Yindobil; Chesneau, Christophe (Journal of Informatics and Mathematical Sciences, 2025)
In this paper, among other things, we establish arithmetic, geometric and harmonic mean inequalities for derivatives of the generalised exponential integral function. The methods of proof rely heavily on monotonicity properties of certain functions associated with the generalised exponential integral function. The results obtained generalise some existing results in the literature.